Moral violations lead to demeaning: Non-disclosure of HIV undermines perceived psychological needs - Alireza Taqipanahi; Morteza Erfani Haromi; Fatemeh Shahri; Alexander Landry; Seyed Nima Orazani (PLoS ONE, 2025)
Dehumanization of stigmatized groups is a pressing social challenge, and to effectively address it, we must understand how it arises. Here, we identify social-cognitive antecedents of a subtle form of dehumanization known as demeaning —which occurs when a target’s “uniquely human” psychological needs (e.g., for meaning in life) are downplayed relative to their physiological needs shared with other animals. We study how demeaning arises by leveraging the Agent-Deed-Consequence (ADC) framework of moral cognition, which posits that perceptions of an Agent’s Deeds, and the Consequences of these Deeds, independently shape perceptions of the Agent’s moral character. Because morality is fundamental to perceptions of humanity, we reasoned that the perception of (im) moral character, in turn, would impact demeaning (i.e., downplaying the Agent’s psychological needs). We support this notion in a vignette experiment in a context where stigma is rampant and crucially understudied—Iran. Participants ( N = 272) evaluated a stigmatized Agent—an HIV-positive individual with a history of addiction. We varied the Agent’s Deed (deceiving partner vs. being honest with a partner) and its Consequence (infecting partner with disease vs not) in a 2 x 2 design. Indeed, a negative Deed and Consequence led to greater perceived immorality. Immorality, in turn, influenced perceptions of the Agent’s “uniquely human” needs, but not their “lower” physiological needs shared with animals. Moreover, our Iranian participants’ perceptions of what is a “uniquely human” need differ from those in previous Western samples, underscoring the need for further investigation into the sociocultural forces influencing dehumanization.